2013
DOI: 10.1242/jeb.095539
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated leptin antagonist with strong orexigenic activity in mice is not effective in chickens

Abstract: A chicken gene orthologous to human leptin receptor (LEPR) has been characterized and found to be active in leptin signaling in vitro in response to a variety of recombinant leptins and leptin-containing blood samples. However, the endogenous ligand of chicken LEPR (cLEPR) -the putative chicken leptin -has been reported by us and others to be undetectable at the DNA, mRNA, protein and activity levels. These reports have raised questions as to cLEPR's role. Here we analyzed the effects of a pegylated superactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
(95 reference statements)
2
3
0
Order By: Relevance
“…The leptin gene was not identifiable in the latter, however we were able to download and assemble the matching SRA sequence reads (Figure 2), which correspond to an intact exon 3 structure. We repeated the sequence searches against the chicken genome and confirmed that even this galliforme LEP -like sequence is not detectable in Gallus gallus , in agreement with the observation that administration of a leptin antagonist had no effect on appetite and body growth of layer chickens [31]. We could not associate any ESTs or RNA-seq reads to the quails’ leptin-like genes and moreover the role of the leptin signaling pathway may differ in galliformes [28].…”
Section: Resultssupporting
confidence: 69%
“…The leptin gene was not identifiable in the latter, however we were able to download and assemble the matching SRA sequence reads (Figure 2), which correspond to an intact exon 3 structure. We repeated the sequence searches against the chicken genome and confirmed that even this galliforme LEP -like sequence is not detectable in Gallus gallus , in agreement with the observation that administration of a leptin antagonist had no effect on appetite and body growth of layer chickens [31]. We could not associate any ESTs or RNA-seq reads to the quails’ leptin-like genes and moreover the role of the leptin signaling pathway may differ in galliformes [28].…”
Section: Resultssupporting
confidence: 69%
“…However, the existence of functional LEP genes in chickens, Japanese quail and the mallard duck has yet to be proven . suggest that this may be associated with changes in appetite regulation linked to domestication, and that it is in line with the observation that a pegylated leptin antagonist that inhibited activation of a LEPR bioassay reporter system by rock dove leptin was ineffective in altering food intake and body mass in chickens (Gertler et al, 2014). However, that conclusion is dependent on LEP having a physiological role in energy balance regulation in the chicken, which may not be the case.…”
Section: Regulation Of Agrp and Pomc Gene Expression By Leptinsupporting
confidence: 65%
“…Interestingly, we noted that avian leptin mRNA is predominantly expressed in the brain and pituitary, but undetectable in peripheral tissues including adipose tissue [ 63 ]. This finding, together with little effect of icv injection of leptin on food intake of chickens [ 68 , 69 ], also points to a possibility that unlike that in mammals, metabolic signal(s) other than leptin associated with negative energy balance from peripheral tissues may control c CART1 mRNA expression in chicken hypothalamus ( Fig 6 ).…”
Section: Discussionmentioning
confidence: 97%